A função materna na transmissão do nome do pai e o adolescente em conflito com a lei - Xavier, Rejane Botelho Teodoro (2010)
This work aims to reflect on the maternal role, specifically in regard to the question of how the discourse of the mother, in cases of adolescents in conflict with the law, has allowed or not the transmission of the Name of the Father. Also is considered that the contemporary family configurations, have dimensions different from those that led to theories of the Oedipus Complex. At this scope we analyzed how this affects the teens when his mother, acting as Another Primordial will be questioned again and when the teenager also separate themselves from their primordial objects. Taking as reference a psychoanalytic reading, we analyzed the configuration of four families in which teens were fulfilling socio-educational measures for Assisted Freedom, allowing the collection of qualitative information such as the various dimensions of femininity, from where it was possible to understand the construction of the Another Primordial and the desiring subject who operated the transmission of the Name of the Father The results showed a family operation guided by flattening of the relationship between parents and children in contemporary society and the fragility of the appointment father in cases of adolescents in conflict with the law, leading to the adolescent offender act, as a way to do this poor substitutive appointment.